The Efficacy of an Endodontic Instructional Multimedia Program for Enhancing the Knowledge and Skills of Dental Students - Mandana Naseri; Zohreh Ahangari; Yazdan Shantiaee; Javid Rasekhi; Ali Kangarlou (Islamic Dental Association of Iran, 2013)
Background and Aim: Full-scale demonstration of treatment phases on actual patients by an instructor is currently the conventional technique for practical instruction on endodontics. In this method, most students do not get the chance to closely observe the clinical procedure due to the small size of oral cavity. This study aimed at assessing the efficacy of an instructional multimedia program in endodontics for enhancing the knowledge and skills of dental students .   Materials and Methods: In this randomized interventional trial, students taking the course of clinical endodontics were divided into two groups receiving conventional live demonstration alone or in combinationwith an instructional multimedia (DVD). Baseline knowledge of students and their level of knowledge and skills after the intervention regarding practical endodontics were assessed by a pre-test and post-test, respectively. Data were compared between the two groups using Kruskal Wallis test .   Results: No significant differenceswere noted between the two groups in terms of knowledge or practical skills of students. However, the multimedia instruction significantly reduced the number of studentinquiries to instructors for troubleshooting (P<0.001 ).   Conclusion: Due to the lack of a significant difference between the two instructional techniques, the multimedia instruction technique may be successfully used as a complement to current conventional techniques for practical instruction on endodontics .